Visionary strategic leadership : sustaining success through strategic direction, corporate management, and high-level programs - Rainey, David L. (Emerald Publishing Limited : Information Age Publishing, Inc., 2013)
The book represents a dramatic step forward in discussing the principles, processes, and practices of visionary strategic leadership. While most of the existing literature covers the subject from organizational and management perspectives, the book focuses on a holistic view of the corporation and all of the supporting entities and customers and stakeholders. The book addresses new theories, methods and practices that are in line with 21st century dynamics.The book is on the cutting edge of thought and practice. It discusses constructs based on the integration of the social, economic, ethical, technological and environmental considerations. Examples are taken from numerous industries in the U.S., Europe, Pacific Rim and South America. The book portrays the global phenomenon. The discussions are based on real world needs and expectations. There is a huge audience of executives, professionals and practitioners who need to understand the opportunities and challenges of today and in the future. There are scholars, professors and business leaders who will view these perspectives as real world approaches being practiced by global corporations today.